Giant omphalocele associated pulmonary hypertension: A retrospective study - Liu, Tai-Xiang; Du, Li-Zhong; Ma, Xiao-Lu; Chen, Zheng; Shi, Li-Ping (Frontiers in Pediatrics, 2022)
Abstract Background: Omphalocele is a common congenital defect of the abdominal wall, and management of giant omphalocele (GO) is particularly difficult for pediatric surgeons and neonatologists worldwide. The current study aimed to review and summarize the clinical features and prognosis in neonates with GO complicated with pulmonary hypertension (PH), which is associated with increased mortality, while in hospital. Methods: Medical records of infants with GO between July 2015 and June 2020 were retrospectively analyzed. The patients enrolled were divided into PH and non-PH groups based on the presence or absence of PH, and patients with PH were divided into death and survival groups based on survival status. Clinical characteristics and outcomes were compared between groups, respectively. The risk factors for PH were analyzed by binary logistic regression. Results: Sixty-seven neonates were identified as having GO and 24 (35.8%) were complicated with PH. Infants with PH were associated with intubation within 24 hours after birth (p =0.038), pulmonary dysplasia (p =0.020), presence of patent ductus arteriosus (p =0.028), a staged operation (p =0.002), longer mechanical ventilation days (p <0.001), oxygen requriement days (p <0.001), parenteral nutrition days (p <0.001), length of NICU or hospital stay (p =0.001 and 0.002, respectively), and mortality (p =0.001). The results of multivariable logistic regression analysis revealed a staged operation was independently associated with PH. In addition, PH patients of lower birth weight, higher peak of pulmonary arterial systolic pressure and refractory to pulmonary vasodilators (PVD) had increased mortality. Conclusion: PH is a serious complication and significantly increase the mortality and morbidities in infants with a GO. In addition, early and serial assessment of PH by echocardiography should be a routine screening scheme, especially in the neonatal omphalocele population who required a staged surgical repair. Clinicians should be aware that infants with PH who had low weight, severe and refractory PH have a higher risk of death.